Anxiety and Depression in Patients with HIV Encephalopathy - Zokirov Muzaffar (Genius Journals, 2023)
This article examines the level of anxiety and the degree of depression in patients with HIV-associated encephalopathy. The patients were examined using the State-Trait Anxiety Inventory (STAI) and the Hamilton Depression Scale .
Keywords: HIV infection; HIV; encephalopathy